∗Šēm∗ and Transcendence: A Transdisciplinary Approach to Biblical Theonyms, from Contextual Monolatry to Trinitarian Revelation - Randrialiva Soanirina Seheno; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2027)
This transdisciplinary investigation analyzes the ontological density and evolutionary dynamics of theonymy within the Old Testament, conceptualizing the divine name (šēm) not as an arbitrary linguistic convention, but as the supreme theophanic locus for the disclosure of Transcendence. By articulating Semitic philology, the diachronic deconstruction inherent to the historical-critical method, and a rigorous intertextual hermeneutique, this study confronts the Masoretic text with the epigraphic sources discovered at Ugarit. It retraces the textual and historical transition from an inclusive monolatry, deeply anchored in the Ancient Near Eastern milieu, toward the prophetic affirmation of an absolute and exclusive monotheism forged during the systemic crisis of the Babylonian Exile. Furthermore, the analysis demonstrates the profound theological continuity uniting both Testaments, wherein the dogmatic reformatio of the Christian Trinitarian synthesis and the Christological